The Rise of Cyber Warfare - Andrian Willyan Djaja (Perhimpunan Intelektual Muslim Indonesia, 2020)
A war in cyber domain has been already started, and its impact is quite devastating. Dangers arisen from the new kind of war ranged from economic disaster such financial accounts shutted or locked, technological problems, for example personal computer hacking and thievery of important data, also includes hacking into a country’s defense system and its use for personal benefit of a country or organization. The recent rise of 5G technology increases the possibility of these dangers to happen in real world. China currently holds the best 5G technology in the world in the hands of its leading company, Huawei. Heated politics between the US and China makes the possibility for China to use its technological advantage against its Western rivals and the whole world becomes very big. The US and its allies will definitely be retaliating against China with their own cyber weaponry, resulting in a large scale cyber warfare.